Isolation, characterization and molecular docking of novel umami and umami-enhancing peptides from Ruditapes philippinarum. (1st May 2021) - Zhang, Yue; Gao, Xinchang; Pan, Daodong; Zhang, Zhiguo; Zhou, Tianqiong; Dang, Yali
Highlights: 14 umami and umami-enhancing peptides were the first identified. KSAEN and QIEELEGK displayed strong umami taste. PAATIPE and HNESQN showed a good capacity of umami-enhancement. Ser123 played key roles in the both model with or without MSG. New way to study the synergistic effect by sensory evaluation and molecular docking. Abstract: To understand the taste of the Ruditapes philippinarum, 14 novel umami peptides were isolated and identified by gel chromatography, HPLC and UPLC-ESI-QTOF-MS/MS. Separations were combined with sensory evaluations and electronic tongue determinations. The peptide sequences were GRVSNCAA, SEEK, KEMQKN, KSAEN, QIEELEGK, TDVEQEGD, HNESQN, RGEPNND, TGDPEK, KGGGGP, TYLPVH, PAATIPE, GPAGPAGPR and AGAGPTP. All peptides had umami and umami-enhancing qualities, KSAEN and QIEELEGK had higher sensory evaluation than the others, while PAATIPE and HNESQN had the best umami-enhancing taste in a 0.35% MSG solution. Molecular docking of the peptides with T1R1/T1R3 indicated that Ser123, Ser146 and Tyr143 may be important in the interaction of the peptides with T1R3. Arg303, Ser123 and Asp166 appear to be involved in the synergistic effect of umami peptides combined with monosodium glutamate. The omission test and the addition test confirmed that the 14 umami peptides contributed to the umami taste of R. philippinarum .